Features of Water Diplomacy in Central Asia - G. Ch. Akunova (Проблемы постсоветского пространства, 2021)
Water issues are traditionally one of the most complex and controversial issues in Central Asia. Over the 30 years since independence, the five republics have not been able to come to a single agreement on the use of water resources. Mainly because their interests do not coincide. The region is conventionally divided into agricultural and energy republics. Some need to irrigate their lands, others are interested in producing electricity. Each of the five republics strives to take into account primarily its own interests, sometimes disregarding the interests of its neighbors. The article deals with the problems of the development of water diplomacy between the states of Central Asia. It is noted that this problem is relevant for the region due to the peculiarities of the position and legal regime of transboundary rivers in Central Asia.